Fetal Mummification in a Friesian Holstein Cow in West Bandung Regency: A Case Report - Satrio, Faisal Amri; Aulia, Anis; Rasyida, Ghinna Aulia; Bari, Fathul; Septiyani, Septiyani; Setyowati, Endang (Hasanuddin University, 2025)
This report describes a case of fetal mummification in a Friesian Holstein cow on a smallholder farm in Indonesia. The cow, in its second pregnancy at approximately four months of gestation, had exhibited vaginal discharge for about 10 hours before examination. Clinical inspection revealed a reddish-brown discharge from the vagina, and the cow was found in sternal recumbency. Per-vaginal palpation showed that the cervix was dilated to approximately a hand's width. The palpation also indicated the absence of fremitus, fetal movement, fetal reflexes, placentomes, and amniotic fluid. The fetus was palpable, dry, and firm. Management of the case involved the extraction of the fetus along with the placenta. Pathological findings included the absence of amniotic fluid, a reddish-brown placenta, and a dry fetus with fully developed and intact bones, which had a blood-like odor but was not foul-smelling. The post-treatment included intrauterine administration of Neo-Kotrimok® (four boluses) and an intramuscular injection of Vitol-140® (10 mL). The prognosis was classified as fausta-dubius. Based on anamnesis, clinical examination findings, and pathological findings, the cow was diagnosed with fetal mummification, a reproductive disorder affecting pregnancy.